Dental Students' Reflections on Quality of Periodontal Care in Dental School Clinics. Issue 1 (1st January 2017) - Chandrasekaran, Sangeetha; Powell, Charles; De la Rosa, Laurice; Mittal, Anuj; Johnson, Lonnie
Abstract : The aim of this study was to analyze dental students' descriptions of and reflections on the periodontal care they provided for their patients in dental school clinics. All students enrolled in the final year of the DDS program in 2011–14 at the University of Colorado School of Dental Medicine were required to complete a self‐assessment of the periodontal care they provided for patients. Assessments from 263 students were compiled and qualitatively analyzed. The key reasons given for not providing good care were identified and then stratified as student/school‐dependent or patient‐dependent factors. Among these students, 63.1% reported that the periodontal care they provided for their patients was inadequate. Some of the student/school‐dependent factors were multiple providers involved in patient care (22.8%), student oversight (21.3%), licensure and academic requirements (20.9%), limited clinic operator sessions (19.4%), clinical rotations to other sites (18.3%), and students' interest in/emphasis on other areas of dentistry (17.9%). Some of the patient‐dependent factors were patient scheduling compliance (61.6%), patient finances (46.4%), medical status (20.5%), urgent dental needs (18.3%), emphasis only on restorative care (17.5%), periodontal care awareness (16.4%), and patients' oral hygiene compliance (11.5%). This analysis of students' attitudes, challenges they faced, and patient‐related factors that influenced the delivery of periodontal care helped to facilitate changes in the curriculum and school policies to optimize clinical instruction and patient care in periodontics.